Heterogeneous price commitments - Saara Hämäläinen (Helsinki Graduate School of Economics, 2023)
We provide a theory of dynamic oligopoly pricing with heterogeneous price technologies, captured by the presence of trackers (on the firm-side) and shoppers (on the consumer-side) who can costlessly follow market prices. Our paper contributes to reconciling the variation in observed price dynamics. Due to the limit pricing resembling price behavior of non-trackers, the equilibrium price distribution can feature gaps and an atom. A price war may erupt, collusion is possible, or prices can remain unchanged for a while. Since the equilibrium price distribution is contingent on the number of trackers, our study puts forth several testable hypotheses to explore the impact of trackers. We also find that, although tracking diminishes consumer welfare and incentives for searching, trackers only benefit from the wider presence of other trackers up to a point.
Keywords: D43; D83; L11; L41; 330; Dynamic oligopoly; price dispersion; price monitoring; commitment; price cycles; collusion; limit pricing